No small potatoes : Junius G. Groves and his kingdom in Kansas - Bolden, Tonya; Tate, Don (New York : Alfred A. Knopf, 2018)
The life of Junius G. Groves, a sharecropper in Kansas who grew a modest potato farm into a potato kingdom.
School Library Journal starred, September 2018
Kirkus Starred, August 2018
Booklist, September 2018
Horn Book, September 2018
Bulletin (Center for Children's Books), October 2018
Includes bibliographical references.
Keywords: Groves, Junius G., -- 1859-1925 -- Juvenile literature; Slaves -- United States -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Kansas -- Biography -- Juvenile literature; Groves, Junius G., -- 1859-1925.; Farmers; Slaves; African Americans -- Biography; Edwardsville (Kan.); Biographies; Nonfiction picture books